Adoption readiness in service innovation: the case of digital money. Issue 4 (18th May 2016) - Thomas, Llewellyn D. W.; Vernet, Antoine; Gann, David M.
Abstract: One challenge for firms seeking to develop new services is to understand the conditions likely to affect the rates of adoption. Understanding relative degrees of 'adoption readiness' provides innovators with information to choose market segments and indicates opportunities to influence adoption environments. However, there is a little research into the adoption readiness of countries upon which firms can base their new service development decisions. This paper considers these issues through the case of digital money, a service innovation some claim to have the potential to provide major economic and social benefits. Defined as 'currency exchange by electronic means', we conceptualise digital money as a socio-technical system, and propose a Digital Money Readiness Index. This composite index integrates institutional, financial, technological, economic, industrial and social attributes to measure adoption readiness. We identify four stages of readiness and systematically analyse the factors that drive under or over adoption of digital money technologies.